Synergistical Effects of Ethanol and Sodium Metabisulfite Treatments on the Physico-chemical Characteristic of Sorghum Kafirin - Yingqi LAN; Xuejian SONG; Zhijiang LI; Lingyan DAI (Shipin gongye ke-ji, 2025)
In order to explore the effects of synergistic ethanol and sodium metabisulfite (SMB) treatments on structure and function of Sorghum kafirin, secondary structure, subunit type, free sulfhydryl, disulfide bond, water- and oil-holding capacity were evaluated through single factor experimental method under various treating conditions. Results showed that, with increasing ethanol concentration and SMB addition, the free thiol content and surface hydrophobicity of Sorghum kafirin were both first increased and then decreased, while a converse trend of disulfide bond content was detected. When the ethanol concentration was 70% and the addition of SMB was 0.2 g, the content of free thiol in the treated Sorghum kafirin was significantly increased to 33.90±0.88 μmol/g (P<0.05), and the content of disulfide bonds was significantly decreased to 3.02±1.10 μmol/g (P<0.05), the spatial structure of Sorghum kafirin was fully opened, the types of small molecular subunits and the content of random coil were increased. Meanwhile, the hydrophobic amino acids were exposed, and the surface hydrophobicity, solubility, and oil-holding capacity of Sorghum kafirin were significantly increased (P<0.05). While the change of water-holding capacity of Sorghum kafirin was not significant in comparison with the defatted Sorghum (P>0.05). These findings suggest that synergistical treatments with ethanol and SMB on Sorghum kafirin could improve its spatial conformation and physico-chemical characteristics, providing a reference for the application of Sorghum kafirin.